2017
DOI: 10.1007/s11894-017-0597-2
|View full text |Cite
|
Sign up to set email alerts
|

Going Gluten Free: the History and Nutritional Implications of Today’s Most Popular Diet

Abstract: Currently, about a quarter of the population reports keeping a GFD despite GRDs affecting less than half of these individuals. Reduced intake of calcium, B vitamins, and fiber as well as enhanced consumption of fat and simple carbohydrates has consistently been reported and needs to be continually addressed. Although a necessity in proper management of GRDs, unforeseen nutritional complications may develop in patients who are gluten free for which enhanced physician awareness is vital to achieving optimal pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 55 publications
1
41
1
4
Order By: Relevance
“…26,27 Furthermore, it is important to realize that Fabiani et al published their study as far back as 2000, since which the gluten-free diet has become popular and easier to maintain. 28 More studies in different populations are needed, but we here demonstrated that, in favorable circumstances, the achievement of good long-term dietary adherence is possible in screen-detected patients. Furthermore, screened patients had similar or even better health-related behavior, when for example smoking was less common among them.…”
Section: Discussionmentioning
confidence: 67%
“…26,27 Furthermore, it is important to realize that Fabiani et al published their study as far back as 2000, since which the gluten-free diet has become popular and easier to maintain. 28 More studies in different populations are needed, but we here demonstrated that, in favorable circumstances, the achievement of good long-term dietary adherence is possible in screen-detected patients. Furthermore, screened patients had similar or even better health-related behavior, when for example smoking was less common among them.…”
Section: Discussionmentioning
confidence: 67%
“…The same problems exist when people eat out as the knowledge of coeliac disease varies substantially in restaurants and cafes and this affects the availability and quality of gluten‐free options. Fortunately, the gluten‐free diet has also become more popular amongst people in the general population in recent years, making products cheaper and easier to find than before . Having said that, there is often confusion between people who choose to follow the trend to avoid gluten and those who do so because they have coeliac disease and need to follow a strict diet.…”
Section: Effects and Acceptance Of A Gluten‐free Dietmentioning
confidence: 99%
“…A gluten-free diet (GFD) is the only established treatment for coeliac disease, which has been used since the 1950s to improve symptoms and intestinal mucosal healing (15). As the spectrum of gluten-related disorders has evolved and interest in using a GFD in IBS has emerged, there has been an increase in the numbers of people following this diet (16). This change is not confined to clinical practice, with increasing numbers of healthy people benefits (16).…”
Section: Gluten-free Dietmentioning
confidence: 99%